Glasgow coma scale components as predictors of outcomes in conservatively managed head injury patients: a prospective observational study - Sapkal, Akshay Satish; Subhedar, Ajay Dnyanoba; Mujawar, Parvez Abdul Jabbar (International Journal of Research in Medical Sciences, 2025)
Background: Traumatic brain injury remains a leading cause of mortality and morbidity worldwide. The Glasgow Coma Scale (GCS) serves as a fundamental tool for assessing neurological status and predicting outcomes in head injury patients. To assess individual components of the Glasgow Coma Scale and identify which parameter demonstrates the most favorable outcome in conservative management and to compare GCS scores at admission, discharge, 3 months and 6 months post-injury. Methods: This study was conducted at a tertiary care center in over 18 months. 164 patients aged 18-60 years with head injuries managed conservatively were enrolled. GCS scores were recorded at admission, discharge, 3 months and 6 months. Statistical analysis was performed using paired t-tests and chi-square tests, with significance set at p<0.05. Results: Majority were males (90.9%) with a mean age of 35.2 years. Road traffic accidents accounted for 45.7% of injuries. At admission, 56.7% had severe head injury (GCS 3-8), 41.5% moderate (GCS 9-12) and 1.8% mild (GCS 13-15). Overall mortality was 7.9%. By 6 months, 91.5% achieved near-normal function (GCS 13-15). Paired t-tests revealed significant improvement in all GCS components: eye response (+1.66 points, p<0.001), verbal response (+2.23 points, p<0.001) and motor response (+2.44 points, p<0.001). Conclusions: Conservative management yields excellent outcomes in appropriately selected head injury patients. The motor component of GCS demonstrates superior prognostic value and should be emphasized in clinical decision-making.